Creations de UiTM : International Mega Innovation Carnival 2022 e-Proceeding Book - UiTM, Pusat Asasi (Pusat Asasi, UiTM Cawangan Dengkil, 2022)
CREATIONS de UiTM: INTERNATIONAL MEGA INNOVATION CARNIVAL 2022 is a program by Pusat Asasi, UiTM Dengkil that provides the golden opportunity for innovators from all walks of life to showcase their creativity skills and the spirit of innovation. This program is open to both international and Malaysian innovators with the aim of providing exposure and experience with various academic content on innovation that are not only interesting but also useful. This virtual presentation box will include not only competitions for innovation, but also exhibitions of innovative ideas/products/inventions from around the globe. Around 150 innovation projects will be showcased to compete virtually, with participation from school students, university students, and innovators from all over Malaysia and around the world.